Prodromal dreams - McNamara, Patrick (Frontiers in Psychiatry, 2025)
I present a provisional model and promising evidence, pending robust longitudinal validation, for the possibility of prodromal dreams: dreams that predict onset of illness before overt symptoms appear. Interoceptive signals are compressed and summated/integrated within brain networks that are most highly active during REM sleep. If there is a bodily problem an error signal is generated and the brain then attempts to infer a cause or explanation for the distortions in the bodily image. It is this picture or updated model of the body (which attempts to depict or explain the distortions or errors in bodily senses) which I suggest then gets depicted in dreams. Prediction error can be remedied either via active inference leading to corrective action, or by model updating—generating models that explain away the error. I suggest that the depiction of the cause of the predictive error (bodily distortions) emerges in dreams (typically with picture language or metaphor) and thus can be interpreted to help diagnose emerging illnesses. The active inference portion of the model updating process on the other hand will depict potential solutions to the predictive error and if this information emerges in dreams these dreams might plausibly contain information to ameliorate/treat the causes of the bodily distortions.